Advancing depression treatment: the role of sigma receptor ligands - Zhang, Peng; Ning, Zeqiong; Chen, Haixia; Chen, Jia; Lu, Zhihong; Xu, Feifei (Frontiers in Neuroscience, 2025)
Depression, one of the most prevalent neuropsychiatric disorders, continues to pose escalating global health challenges. Despite the discovery of numerous antidepressants, their clinical applications are limited, and there is still an urgent need to identify more effective antidepressant drugs and their molecular targets. In recent years, sigma receptors have garnered considerable interest among depression researchers because of their diverse biological functions and significant roles in the central nervous system. This review provides a comprehensive summary of the potential roles of sigma receptors and their ligands in the pathogenesis of depression and the course of antidepressant treatment, with the aim of offering insights into further research and potential therapeutic development.